Faktor-Faktor Yang Berhubungan Dengan Kekambuhan Skizofrenia Di Wilayah Kerja Puskesmas Kumun - Ramadhani, Nike; Wati, Del Fatma; Amelia, Sherly (REAL in Nursing Journal, 2022)
Background: Schizophrenia is a functional form of psychosa with major disorders of thought processes, affect / emotion willpower and psychomotor accompanied by distortion of reality, One of the problems of handling in schizophrenia is recurrence, the impact of schizophrenia recurrence will certainly harm and harm others. The purpose of this study was to find out the relationship of family support factors and drug adherence to schizophrenia recurrence in the working area of Kumun Health Center. Methods: This research uses quantitative types with descriptive analictic research designs through a cross sectional approach. The population in this study were all families who had families suffering from schizofenia in the working area of the Full River kumun health center. With a population of 308 people. Sampling using the purposive sampling method with a sample of 75 people. Data collection using questionnaires. The stage of data processing through editing, coding, processing, cleaning data. Results: The results found no association of family support (Pvalue= 0.963) to recurrence, and no association between drug adherence (Pvalue= 0.004) to recurrence. Conclusion: It is recommended to the Kumun Health Center to improve education about the importance of taking medicine